MEMBANGUN INSTRUMEN EVALUASI YANG BERKUALITAS MELALUI ANALISIS TINGKAT KESUKARAN, DAYA BEDA, DAN EFEKTIVITAS PENGECOH SOAL - Laila Febriani; Riri Safitri; Cinta Hamidah; Juli Anisah; Sholatul Ramadhana; Ahmad Husein; Fitrah Al Fatih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the importance of difficulty level, discrimination index, and distractor effectiveness analysis in developing high-quality educational evaluation instruments. The quality of test items plays a crucial role in ensuring that evaluation results accurately and objectively measure students’ abilities. This study employed a library research method by utilizing various references, including books, scientific journals, and other relevant literature related to item analysis. Data were collected through reviewing, analyzing, and synthesizing theories concerning test item quality. The findings indicate that the difficulty level serves to classify items based on their degree of ease or difficulty, the discrimination index measures an item’s ability to distinguish between high-achieving and low-achieving students, while distractor effectiveness evaluates the functionality of incorrect answer options in multiple-choice tests. These three aspects are interconnected and serve as key indicators in determining the quality of an evaluation instrument. Test items with balanced difficulty levels, strong discrimination power, and effective distractors provide more accurate information regarding students’ learning outcomes and competencies. Therefore, item analysis should be conducted continuously to improve the validity, reliability, and overall quality of educational assessment instruments. The implementation of systematic item analysis contributes significantly to the development of more effective, objective, and accurate evaluation practices in educational settings.